Students’ motivation types in the smart approach to ESP instruction - Simonova, Ivana; Prochazkova, Zuzana; Lorenc, Vladimir; Skoda, Jiri (Australasian Journal of Educational Technology, 2021)
This article focuses on the smart approach applied in teaching two topics (referred to as learning contents) within English for Specific Purposes with regard to students’ motivation types. It introduces results of the research conducted in this field. The research is based on the definition of the term smart set by Silverio-Fernandez et al. (2018) and the theory of motivation types created by Plaminek (2010), who designed the standardised Motivation Type Inventory distinguishing four motivation types (accurators, coordinators, directors, explorers). Data were collected via didactic tests; quantitative methods were applied to calculate the potential increase in students’ knowledge as a difference between pre-test and post-test scores in the didactic tests. In total, 119 prospective teachers from the Faculty of Education and the Faculty of Science at Jan Evangelista Purkyne University participated in this research conducted via quasi-experimental ex-post-facto method for 12 weeks. The smart approach included the exploitation of smart devices and technologies (applications) in face-to-face instruction and in-home preparation for lessons. Three main hypotheses were set to prove whether the smart approach to ESP instruction can be applied to learners of all motivation types. According to the findings, the smart approach suited students of all motivation types; however, coordinators’ increase in knowledge was significantly higher compared to explorers and directors in one of the learning contents<s>.</s>